(untitled) (Elmergib Journal of Human Sciences, 2025)
Linguistic Analysis of Similar Verses in the Holy Quran A Descriptive-Analytical Study This research examines similar verses in the Holy Quran from a grammatical perspective, highlighting the subtle differences in grammatical structure that lead to differences in meaning despite the apparent similarity in wording. The researcher adopts a descriptive-analytical approach, reviewing examples of these verses and deconstructing their grammatical structures to clarify the secrets of Quranic expression. The research demonstrated that Quranic grammar transcends rigid rules, expressing a high degree of linguistic flexibility that interacts with the context and situation, contributing to the construction of meaning in a precise and effective manner. It also demonstrated that studying this phenomenon opens new horizons for understanding the Quranic text and rehabilitates grammar as a tool for understanding meaning, not merely formal rules.